Emerging Research on the Implications of Hormone Replacement Therapy on Coronary Heart Disease - Keck, Carson; Taylor, Marian (Current atherosclerosis reports, 2018)
Purpose of Review Cardiovascular disease (CVD) is known to be an increasing cause of mortality among women, particularly postmenopausal women. Hormone replacement therapy (HRT) is a topic that has been investigated over the past decade for its known impact on the cardiovascular system. This review summarizes the evidence and current opinion on the associations between HRT and CVD, evidence both supporting and against HRT use as a prevention to the development of coronary heart disease (CHD). Recent Findings The majority of the new data available suggests the use of HRT has the potential to be more beneficial in the prevention of CVD if started in women at younger ages. Current studies also suggest that while starting HRT in older postmenopausal women may be associated with an initial slight increase in CVD, the overall lifetime occurrence rate is not increased. Several studies have also started to use the “timing hypothesis” to suggest that HRT initiated soon after menopause has the potential of being the greatest cardiovascular benefit to the patient. Overall, the data support the finding that HRT should be used only for symptomatic treatment, not in an attempt to slow progression of CVD. Summary Current evidence does not support the use of HRT for either primary or secondary prevention of CHD. HRT has different implications based on the temporal relationship in which it is initiated in relation to the onset of menopause. Overall, the use of HRT should be an individualized decision with each patient on the basis of the individual’s symptoms and overall risk profile.